1998
DOI: 10.1001/archotol.124.9.1021
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Cauterization for Treatment of Fourth Branchial Cleft Sinuses

Abstract: Fourth branchial cleft sinuses are rare, and the nature of their origin is controversial. Clinical presentation is varied because they may present as asymptomatic neck masses, recurrent neck abscesses, or suppurative thyroiditis. We describe herein 7 children who presented with abscesses on the left side of their necks, 3 of whom had abscesses that involved the thyroid gland. Direct laryngoscopy revealed that all 7 children had a sinus tract opening into the apex of the piriform sinus. Endoscopic obliteration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 8 publications
2
89
2
1
Order By: Relevance
“…We first proposed endoscopic electrocauterization as a definitive treatment for PFST in 1998 and subsequently reported on 10 cases involving the procedure in 2004. 4,11 The procedure is described in detail in our previous reports. 4,11 With continued clinical experience since our initial report, we have found that cauterization alone without balloon dilation of the sinus tract seems to be equally efficacious ( Figure 1).…”
mentioning
confidence: 99%
“…We first proposed endoscopic electrocauterization as a definitive treatment for PFST in 1998 and subsequently reported on 10 cases involving the procedure in 2004. 4,11 The procedure is described in detail in our previous reports. 4,11 With continued clinical experience since our initial report, we have found that cauterization alone without balloon dilation of the sinus tract seems to be equally efficacious ( Figure 1).…”
mentioning
confidence: 99%
“…This technique has been also successfully applied in four of five newborns by Leboulanger et al, 4 and has been reported in a recent publication. However, other endoscopic techniques have also been successfully performed by other authors in older children using electrocauterization, 15 trichloroacetic acid 16 or silver nitrate. 7 Although rare, the neonatal form of a fourth branchial pouch anomaly is a clinical entity that should be known by pediatric practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…One month after the drainage operation, Therefore, we diagnosed this case as left pyriform sinus fistula infection resulting in a deep neck infection and acute suppurative thyroiditis. Recently, an endoscopic chemocauterization technique has been described [4][5][6][7]. However, because we consider that operative excision of the entire tract, including the adjacent thyroid tissue, is essential to prevent recurrence, we performed a surgery using a lateral cervical approach.…”
Section: Case Reportmentioning
confidence: 99%